Prevalence and Risk Factors for Hearing Loss in Chilean Shellfish Divers - Marie Astrid Garrido Campos; Benedikt Anselm Hindelang; Denise Siqueira de Carvalho; Ilse Urzúa Finke; Ronald Herrera; Katja Radon (Ubiquity Press, 2018)
Background: Diving within artisanal fishing is a profession carried out by many men in coastal communities of southern Chile. These shellfish divers use surface supplied air for breathing. Among potential health threats are occupational accidents, decompression sickness and barotrauma. Repeated middle and inner ear barotrauma and decompression sickness of the ear may result in hearing loss. Objective: To determine the prevalence of hearing loss and related risk factors in artisanal shellfish divers. Methods: A cross-sectional study including 125 male shellfish divers was carried out in a coastal village in southern Chile. Participants were interviewed using a standard Spanish questionnaire adapted for this population. Hearing loss was assessed through audiometry. Any hearing loss, sensorineural hearing loss and other types of hearing loss (conduction, unilateral and mixed) were used as the outcomes. Bivariate and multiple logistic regression models were carried out to identify risk factors for hearing loss. Findings: Median duration on the job was 25 years (range 1-52), 64% of divers had a low level of schooling and 52% reported not knowing how to use decompression tables. Most (86%) of the divers dove deeper than 30 meters exceeding the 20 meters permitted by law. The majority (80%) reported having experienced several episodes of type II decompression sickness during their working life. The prevalence of any type of hearing loss was 54.4%: 29.0% presented sensorineural hearing loss and 25.6% presented other types of hearing impairment. After adjustment for age and other potential risk factors, diving more than 25 years was the main predictor for all kinds of hearing loss under study. Conclusions: Hearing loss is frequent in artisanal shellfish divers and safety measures are limited. Although based on small numbers and lacking an unexposed comparison group, our results suggest the need for community-based interventions.